Hospital Acquired Infections Among Patients Admitted in the Medical and Surgical Wards of a Non-Teaching Secondary Care Hospital in Northern India - I. Ginawi; Mohd Saleem; Mastan Sigh; A.K. Vaish; I. Ahmad; V.K. Srivastava; A. Fahad Abdullah M. (Journal of Clinical and Diagnostic Research, 2014)
Objective: To investigate the incidence of Nosocomial Infection (NI) and type of bacteriological isolates among the patients admitted in the medical and surgical wards of a non-teaching secondary care hospital in north India. Materials and Methods: This was a cross-sectional hospital based study conducted in the Wards of General Medicine, General Surgery and Orthopaedic of the hospital. The patient were admitted in the department for various surgical procedures, without evidence of initial infection, were included in the study. Results: A total of 176 patients were included in the study of which 82 were from Medical and 94 from Surgical ward. Overall incidence of NI was found to be 26.1% (Medical ward=28%, Surgical ward=24.5%., p=0.58). The isolation rate of Acinetobacter baumannii was (p=0.15) higher among the patients of medical ward (95.7%) than surgical ward (82.6). Escherichia coli was isolated in 89.1% and no significant difference was observed between medical and surgical wards. Klebsiella pneumoniae was isolated in 50% patients and was almost similar (p=0.37) in medical surgical wards. The isolation rate of Pseudomonos aeruginosa, Enterococcus faecalis, Staphylococcus aureus and Coagulase negative staphylococci were 43.5%, 73.9%, 34.8% and 17.4% respectively. A significant difference was observed in the isolation rate of Enterococcus faecalis (p=0.007) and Coagulase negative staphylococci (p=0.002) between medical and surgical wards. Overall, among the patients who developed NI, 27.2% patient’s bacterial isolates were Gram positive (Surgical=64.1, Medical=80%). Conclusion: The incidence of NI is increasing in the hospitals, so extensive that more care has to be taken in cleaning the wards of the hospitals.